Isolation and characterization of multiple drug-resistant bacteria from the waste of hospital and non-hospital environment - Hasan, Mahmudul; Hossain, Md Khaled; Rumi, Nazmi Ara; Rahman, Md Shajedur; Hosen, Md Aoulad (Asian Journal of Medical and Biological Research, 2020)
Antibiotics used in hospitals for patient care which potentially growing antibiotic resistant bacteria in hospital waste and simultaneously transmitting to non-hospital environments by drainage system. Total 20 samples were collected randomly and examined with different bacteriological, biochemical and molecular tests. 55 bacterial isolates were isolated from all samples, among them 32 (58.2%) were from hospital environment and 23 (42.1%) were from non-hospital environment. The result of total viable count showed that maximum countable bacteria (2.20×1010) CFUs/ml that were from MARCH and the minimum number of countable bacteria (1.0×1010) CFUs/ml were isolated from the sample of Kalitola. Among the isolates, E. coli, Pseudomonas spp, Klebsiellaspp, Salmonella spp, Staphylococcus spp and Vibrio spp were identified 16 (29%), 12 (21.8%), 9 (16.4%), 8 (14.5%), 5 (9%) and 5 (9%) respectively. Multidrug resistant (MDR) Pseudomonas aeruginosawas characterized from hospital wastewater by polymerase chain reaction assays targeting the virulence gene and 16S rRNA gene region was amplified with the universal primers. PCR amplification band was found at 1399 bp. The antibiotic sensitivity study revealed that among the hospital isolates, about (83.3%) were resistant against Ampicillin, followed by Amikacin, Kanamycin and Penicillin (77.8%). On the other hand, non- hospital isolates were resistant against Amoxicillin and Penicillin (66.7%) followed by Ampicillin and Vancomycin (58.3%). Both hospital and non-hospital isolates were sensitive to Gentamycin respectively 72.5% and 75%. The findings of the experiment suggested that hospital wastewater contained more MDR bacteria than non-hospital wastewater which are released into receiving water bodies that may cause a serious threat to public health. Reducing indiscriminate use of antibiotics in both hospital and non-hospital settings and the use of wastewater treatment plant (WTP) in a hospital may reduce this problem. Asian J. Med. Biol. Res. September 2020, 6(3): 460-468